PENGARUH PEMAHAMAN MULTI LEVEL MARKETING DAN PRESTASI BELAJAR PADA MATA PELAJARAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA DI SMKN 1 KOTA JAMBI - Mayasari Mayasari (Universitas Batanghari Jambi, 2014)
This study aims to reveal, investigate and analyze about: 1) the influence of Multi Level Marketing understanding of the interest in entrepreneurship students at SMK 1 Jambi, 2) the influence of student achievement in the subjects of entrepreneurship to the interest in entrepreneurship students at SMK 1 Jambi, 3) the influence of understanding multi Level Marketing and learning achievement in the subjects of entrepreneurship to the interest in entrepreneurship students at SMK 1 Jambi.Type of research is quantitative research with this type of correlational research. The population in this study were students at SMK 1 class sales totaled 116 Jambi city. A sample using a sample size according to Krejcie-Morgan so that the sample in this study amounted to 88 students. Data were collected through a questionnaire using a Likert scale that has tested the validity and reliability. Data analysis technique used is multiple linear regression using SPSS (Statistical Package For Social Science) version 16:00Results of the study were: 1) There is a significant difference between the perception of Multi Level Marketing 23.8% interest in entrepreneurship or could be seen through the sig is 0,040 <Sig. 0.05, 2) there is an effect on academic achievement entrepreneurship subjects of interest in entrepreneurship by 15.5%, or could be seen through the sig of 0.038 <Sig. 0.05, and 3) there is an effect of understanding Multi Level Marketing and achievement of business subject to interest of 7.6% or entrepreneurship can be seen through the sig 0.036 <0.05There are some suggestions in this study as follows expected at the school in order to facilitate activities associated with entrepreneurship subjects in schools so that students can practice entrepreneurship, and is expected to subject teachers to pay more attention to entrepreneurship, to guide and direct interest in entrepreneurship students.Keywords: Understanding MLM, Achievement and Interest in Entrepreneurship